Tissue engineering of heart valves: antigen removal from xenogeneic tissue scaffolds - Arai, Shiori, author; Orton, E. Christopher, advisor (Colorado State University. Libraries, 2009)
Tissue-engineered heart valves hold the promise of an ideal heart valve substitute by using appropriate and functional cells and scaffolds. An ideal heart valve should be durable, non-immunogenic, non-thrombogenic, resistant to infection and capable of regeneration and growth. Xenogeneic tissues are potential candidates for scaffolding of tissue-engineered heart valves. Anionic detergent-based decellularization has been employed to eliminate xenogeneic tissue immunogenicity. The present studies were performed to develop a technique to detect antigenic proteins in xenogeneic tissue scaffolds, to evaluate the efficacy of antigen removal of current detergent-based decellularization of xenogeneic tissues, to develop novel techniques to enhance antigen removal, and to address issues related to the cytotoxic effects of sodium dodecyl sulfate (SDS).

To develop a technique that identifies antigens in bovine pericardium (BP) or porcine aortic valve conduit (PAV), immune serum was obtained from rabbits that were injected untreated BP or PAV every two weeks. Immunoblot assay was performed on untreated BP or PAV with the rabbit immune serum. Immunoblot assay identified multiple bands and the banding density increased with 14 day through 70 day post-immune serum. This suggested a specific acquired immunity in rabbits towards xenogeneic tissue with time. The immunoblot-based assay developed in this study was capable of surveying a broad range of potential soluble protein antigens in xenogeneic bioscaffolds.

Detergent-based decellularization was evaluated for its efficacy on removal of antigens from BP or PAV using the developed immunoblot assay. BP or PAV were treated with hypotonic solution, 0 to 0.5% SDS or sodium deoxycholate (SD) followed by aqueous washout. Higher concentrations of detergent improved antigen removal in BP with SDS or PAV with SD; however, neither SDS- nor SD-decellularization resulted in complete removal of antigens based on the developed immunoblot assay.

A novel method for enhancing antigen removal from xenogeneic bioscaffolds was developed. This method, termed solid-phase tissue electrophoresis (TE), was based on the concept of sodium dodecyl sulfate-polyacrylamide gel electrophoresis. TE was performed at 0, 60 or 120V after tissue treatment with various concentrations of SDS. Both SDS concentration and TE treatment significantly enhanced antigen removal from PAV based on two-way ANOVA (p=0.001 or p=0.025 respectively). A significant SDS concentration-TE treatment interaction was not detected. Treatment with 1% SDS and 120V followed by aqueous washout resulted in apparent complete removal of antigens to levels below the detection limit of the immunoblot assay.

To evaluate cytotoxicity of SDS, ovine vascular cells were cultured with various concentrations of SDS for 48 hours. SDS concentrations >10µM reduced the total cell number, while concentrations >100µM reduced the percentage of live cells of ovine vascular cultured cells. SDS concentrations were measured in the washout solution of SDS-treated BP. SDS leached from SDS-treated BP at concentrations that are potentially cytotoxic. The extent of SDS leaching was dependent on the SDS concentration used for tissue treatment, and diminished over 96 hours.

In conclusion, significant issues were identified with current detergent-based decellularization methods for xenogeneic bioscaffolds with regard to the completeness of antigen removal and cytotoxic effects of detergents. TE may address one of these issues by significantly enhancing antigen removal from detergent-treated xenogeneic bioscaffolds.
Keywords: antigen removal; heart valves; tissue engineering; tissue scaffolds; xenogeneic tissue; biomedical engineering; medicine